PSYCHOLOGICAL AND ARTISTIC STYLE IN OLMAS UMARBEKOV’S PROSE: AN ANALYSIS OF “SEVGIM–SEVGILIM” - Shokirova Mohinur Murod kizi (International Journal of Literature and Language Studies, 2026)
In this article, Olmas Umarbekov’s prose and the short story “Sevgim–sevgilim” are analyzed from the perspective of complex artistic psychologism as an integrated system of expressive means. The study examines how internal monologue, dialogue, psychological detail, and psychological parallelism function together to reveal the emotional and psychological depth of the narrative. The research demonstrates that Umarbekov’s narrative technique extends beyond simple storytelling and forms a structured artistic system that reflects the complexity of human emotions and inner conflicts. The analysis shows that the protagonist’s psychological development is shaped by emotional instability, pride, guilt, and delayed moral awareness, which ultimately lead to irreversible consequences. The findings suggest that Umarbekov’s prose effectively combines psychological realism with artistic expression, allowing a deeper understanding of human behavior and emotional vulnerability.